1999
DOI: 10.1016/s0194-5998(99)70235-4
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Muscle Fiber Types in the Human Thyroarytenoid Muscle: An Immunohistochemical and Stereological Study Using Confocal Laser Scanning Microscopy

Abstract: A decline in motor performance contributes to laryngeal dysfunction in the elderly, but the pathogenetic mechanisms are unknown. Quantitative 3-dimensional, age-related changes in the muscle fiber content of the human thyroarytenoid muscle were estimated from geometric probability (stereology) by use of a technique that provided a statistically unbiased sample of all possible section orientations and locations in the entire muscle volume. There was a preferential 27% age-related loss in the length density (L(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 17 publications
8
86
0
Order By: Relevance
“…The findings of the present study demonstrate that there are regional differences in both parts of the PCA (Figures 6 and 7), which is in accordance with Wu et al 17 Secondly, as suggested by many ''fiber-type grouping'' observed, these phenotypic changes, as in other skeletal muscles, occur by denervation and subsequent reinnervation and/or aging. 21 Histochemical studies of human PCA in elderly patients have already shown the presence of the ''fiber-type grouping,'' which is a result of a degenerative-aging process. 11,12 Generally in this condition, dendritic sprouts from a single motor neuron reinnervate a group of denervated muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study demonstrate that there are regional differences in both parts of the PCA (Figures 6 and 7), which is in accordance with Wu et al 17 Secondly, as suggested by many ''fiber-type grouping'' observed, these phenotypic changes, as in other skeletal muscles, occur by denervation and subsequent reinnervation and/or aging. 21 Histochemical studies of human PCA in elderly patients have already shown the presence of the ''fiber-type grouping,'' which is a result of a degenerative-aging process. 11,12 Generally in this condition, dendritic sprouts from a single motor neuron reinnervate a group of denervated muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…9 Subsequent studies have identified neonatal myosin heavy chain (MyHC) isoform presence with immunohistochemical staining as indicative of muscle regeneration after reinnervation has been established. 10 Normally neonatal MyHC is expressed in adult muscle only in regenerating fibers, 11 as a response to denervation (especially in type IIA fibers), 12 or as a transient response from stretch-induced hypertrophy of muscle.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 A recent histochemical report confirms these earlier results on human TA muscle. 31 Immunohistochemical identification of myosin isoforms has only recently been investigated, and shows that antibodies reactive for type I MHC, general fast type II MHCs, 32 tonic MHCs, 21 and neonatal MHC do react with fibers in human TA muscles. The neonatal MHC is thought to be expressed in regenerating fibers associated with age-related muscle changes, 33 rather than as part of normal protein expression.…”
Section: Myosin Expression In Human Laryngeal Musclementioning
confidence: 99%